Disruption of Oil Palm Empty Fruit Bunches by Microwave-assisted Oxalic Acid Pretreatment - Nissa Nurfajrin Solihat; Fahriya Puspita Sari; Lucky Risanto; Sita Heris Anita; Fitria Fitria; Widya Fatriasari; Euis Hermiati (Institute for Research and Community Services (LPPM) ITB, 2017)
Developing an effective pretreatment for the conversion of lignocellulosic biomass to ethanol is an important effort in reducing the cost of this process. Microwave-assisted pretreatment is considered a green technology that can effectively break down lignocellulosic structures. The objective of this study was to investigate the most effective temperature for microwave-assisted oxalic acid pretreatment regarding the structural characteristic changes of oil palm empty fruit bunches (OPEFB) fibers. The fibers were subjected to microwave-assisted oxalic acid pretreatment at 160